Total Synthesis of Acetate from CO(2) V. Determination by Mass Analysis of the Different Types of Acetate Formed from (13)CO(2) by Heterotrophic Bacteria - Schulman, Marvin (1972)
Mass analysis was used to determine the amount of acetate which is totally synthesized from (13)CO(2) during fermentations by Clostridium formicoaceticum, C. acidiurici, C. cylindrosporum, Butyribacterium rettgeri, and Diplococcus glycinophilus. In the fermentation of fructose by C. formicoaceticum, 27% of the acetate was found to be totally synthesized from CO(2), and the remaining acetate was unlabeled, having been formed from fructose. Evidence is presented that the purine-fermenting organisms, C. acidiurici and C. cylindrosporum, totally synthesized about 9% of the acetate from CO(2), and that the methyl group of an additional 9% was formed from CO(2). The remaining acetate was formed from the carbons of the purine and not via CO(2). It has been postulated that the fermentation of the purines and synthesis of acetate from CO(2) both occur via derivatives of tetrahydrofolate. Evidence is presented that a compartmentalization of these folate intermediates is required if both the purine degradation and the CO(2) utilization involve identical intermediates. Neither B. rettgeri nor D. glycinophilus incorporated sufficient (13)CO(2) into acetate to allow determination of the types of acetate by mass analysis, although they did incorporate labeled (14)CO(2) in both positions of acetate.